Is The Public Satisfaction Index (IKM) Related to The Quality of Infrastructure and Facilities in Surakarta City? - Tamara, Anindya Putri; Kertati, Indra; Adimagistra, Tiasa; Sudrajat, Agus Sarwo Edy (Jurnal Pembangunan Wilayah dan Kota, 2025)
As cities grow and diversify, public institutions play a vital role in urban planning, particularly in climate adaptation, infrastructure improvement, and community welfare.  In Indonesia, the Public Satisfaction Index (Indeks Kepuasan Masyarakat—IKM) provides a standardized tool to capture citizens’ perceptions of service quality, thereby influencing policy formulation, resource allocation, and strategies for service improvement. This study aims to provide the government with insights into the relevance of IKM to the quality of public services, particularly in terms of infrastructure and facilities. The research employs a quantitative approach with a descriptive analysis to provide a detailed and comprehensive description of the research population.  The research data utilises IKM measurements in accordance with Regulation 14/2017 of the Minister of Administrative and Bureaucratic Reform, as well as field observations, particularly in relation to infrastructure and facilities. The IKM survey covered 156 public service units with more than 3,000 respondents, while field observations were conducted on 25 purposively selected units. Observational parameters included building condition, service room quality, toilet facilities, completeness of supporting infrastructure, and accessibility for vulnerable groups such as persons with disabilities, the elderly, women, and children.  The results of this research show that there is a relationship between the value of IKM and the quality of facilities and infrastructure in the city of Surakarta. Several aspects, such as the availability and completeness of facilities and infrastructure, especially for people with special needs, have a direct impact on the public satisfaction index.